2009
DOI: 10.1080/02508060903115175
|View full text |Cite
|
Sign up to set email alerts
|

An overview of on-site retention and detention policies for urban stormwater management in the Greater Western Sydney Region in Australia

Abstract: This article presents an overview of on-site retention (OSR) concepts and practices as components of sustainable urban stormwater management within local government organizations (Councils) in the rapidly growing Greater Western Sydney Region. It is found that the policies regarding on-site detention (OSD), OSR and water-sensitive urban design (WSUD) vary significantly across the Councils in this region. Council specifications and guidelines are often inconsistent and inhibit sustainable urban stormwater manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…They carried out the financial viability analysis of the RWHS in single and multi-family buildings and found that in single-family households, an expected payback period would be between 33 and 43 years depending on the tank size, and for a multi-family, building a payback period would be as high as 61 years for a 20 m 3 tank. In Australian studies by van der Sterren et al [10][11][12], it was found that although RWHS would be very useful in providing required water in peri-urban regions of Sydney, water quality would not always meet the required standard in relation to heavy metals and pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…They carried out the financial viability analysis of the RWHS in single and multi-family buildings and found that in single-family households, an expected payback period would be between 33 and 43 years depending on the tank size, and for a multi-family, building a payback period would be as high as 61 years for a 20 m 3 tank. In Australian studies by van der Sterren et al [10][11][12], it was found that although RWHS would be very useful in providing required water in peri-urban regions of Sydney, water quality would not always meet the required standard in relation to heavy metals and pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Such technology could also be used to meet regulatory requirements for on-site detention (OSD). Such site-based OSD requirements are common in Australia [44] and many parts of the world (e.g., [45]). Combining this functionality with rainwater harvesting and restoration of stream flow regimes provides an attractive integrated water cycle solution.…”
Section: Introductionmentioning
confidence: 99%
“…Stormwater could be confined within the system allowing vertical flow of water to underlying soil that the authors opined would have befitted the agenda of sustainability. The purpose of having water storage chamber under the permeable road is similar to have On-Site Detention (OSD) facility [10][11] that is built with a combination of depressions in paved areas for better stormwater conveyance and an underground tank which does not use up land space [12]. Existing gutters, pipes, curbs, and graded surfaces are part of the overall site drainage system which assists in directing stormwater runoff to the StormPav Green Pavement.…”
Section: Methodsmentioning
confidence: 99%